طينة الشعر وتأثيث المعنى السيميولوجي في ''تجليات طين الصمت'' للشاعر مشري بن خليفة - ملاحي, علي (جامعة الوادي - university of Eloued, 2022)
يُشَرِّح هذا المقال رؤية شاعر تتفاعل في مدوناته الشعرية زوايا نظر و ايقاعات شعرية غير عادية.. هناك الكثير من المعنى الزئبقي والكثير من الفيض الشعري والكثير من التشبّع الأسلوبي والكثير من الاستدعاء للرموز الدينية والأنساق القرآنية والكثير من الايثار الجمالي لمفردات وصيغ مفتوحة يتلمسها الخطاب الشعري عند الشاعر مشري بن خليفة، الذي يحضر بقوة في جمله وتراكيبه وصوره وايحاءاته واستعاراته وفي معجمه الذي يتميز بالميل الواضح الى تطويع اللغة من أجل غايات جمالية تستهوي الشاعر، كي يعبر عن وجهة نظره المتفتحة على دواوين الشعر العربي وعلى التراث العربي والإنساني العالمي وفق تقنيات هي في جوهرها ملامح وجدانية تختزل تجربته وتحدد رؤيته وتكشف عن منابع تدفقاته الانسيابية التي تميز خطابه، وتفصح عن طبيعة الرؤية الشعرية التي يجسدها ديوان" تجليات طين الصمت " بشكل دقيق. This article anatomist the vision of a poet interacting in his poetic blog unusual angles of view and poetic rhythms.. There is a lot of mercurial meaning, a lot of poetic Overflow, a lot of stylistic saturation, a lot of invocation of religious symbols and Quranic harmonies, and a lot of aesthetic altruism of open vocabulary and formulas touched by the poetic discourse of Mechri Ben Khalifa.. Which is strongly present in his sentences, compositions, images, suggestions, metaphors and in his lexicon, which is characterized by a clear tendency to adapt the language for aesthetic purposes that appeal to the poet. In order to express his open-minded point of view on the collections of Arabic poetry and on the world human heritage according to techniques that are essentially emotional features that reduce his experience, define his vision and reveal the sources of his fluid flows that characterize his speech. It reveals the nature of the poetic vision embodied by the divan of the manifestations of the clay of silence accurately.
مقال
Keywords: مشري ; الطين ; الصمت ; تجليات ; خريطة ; المعنى; mud ; silence ; manifestations ; map ; meaning